UN agenda on prevention of human rights violations - Boyashov, Anatoly S. (Journal of the Belarusian State University. International Relations, 2020)
Prevention costs less than cure. This wisdom has been recently mainstreamed in the UN system. Prevention lies at the core of the UN reforms. The UN prevention agenda has incorporated the domains of peace and security, development, humanitarian assistance, and human rights. The UN preventive diplomacy has comprised briefings, monitoring bodies, “quiet diplomacy” within the UN Security Council, the UN development group, the UN Secretariat, the World Bank group, the UN office for the coordination of humanitarian affairs, etc. In 2018, a group of states proposed to extend prevention to the UN Human Rights Council – to operationalise it’s mandate to prevent human rights violations. The views on the operationalisation of prevention have diverged. Human rights and conflict caucus under the leadership of Germany suggested using the full preventive potential of the UN human rights instruments by a stronger link between Geneva and New York – through the briefings by the UN Human Rights Council special procedures at the Security Council. The Like-Minded Group recommended to refrain from the review of the existing mandates of the UN bodies and rather to enhance technical assistance and capacity building of states to address the root causes of crises. A few states expressed concerns that prevention might serve as an umbrella for the military component of responsibility to protect. Surprisingly, the agenda has not been suspended: the stakeholders do not quit the agenda and engage constructively in negotiations on the prevention tools. The research puzzle of the article is that while the interrelation of peace and security with human rights might bring a cumulative effect, such an interrelation could also mix the mandates of the UN principal organs and cause the deep structural review of the UN. This article aims to reveal the variety of tools in the UN prevention agenda. What is prevention at the UN system? What are the tools that could be launched for the prevention of human rights violations?